To solve the system of equations by substitution, we'll solve one equation for one variable and substitute it into the other equation.
Let's solve the second equation for x:
x + 3y = -
x = -3y -
Now we'll substitute this value of x into the first equation:
6y + 5(-3y - )= 8
6y - 15y - = 8
-9y - = 8
y = -
Substituting y = into the second equation, we get:
x = -3( - )
x = -3
Therefore, the solution to the system of equations is (x, y) = (-3, ).
Note: Determine whether the solution to the new equation is a solution to the old system of equations by graphing. Use Desmos!
The solution to the original system of equations (is also, is not) a solution to the new equation.
Solve the system of equations by SUBSTITUTION.
6y + 5x = 8
x + 3y = -
1 answer